Scientific drilling in the South Atlantic: International Ocean Discovery Program Workshop; Rio de Janeiro, Brazil, 2-5 April 201 - Santos, Roberto Ventura; Glasmacher, Ulrich A.; Geldmacher, Jörg (Eos, 2014)
The South Atlantic is a classic example of continental breakup in which the mechanisms that drove the initial fragmentation still need to be detailed. Mantle plumes may have played a key role in this process, as implied by the Rio Grande Rise (RGR) and Walvis Ridge (WR) hot spot tracks. Their role in the South Atlantic opening is uncertain, as questions remain about their origin and relationship with the structure and dynamics of the upper mantle. Recent findings indicate that the western margin of continental South America did not behave as a rigid block but instead stretched significantly, allowing the emplacement of igneous and exhumed mantle rocks. Continental rifting may have rafted fragments of the continents into the ocean, as implied by recently dredged continental rocks from the RGR.
Gesehen am 21.01.2021